2021
DOI: 10.3390/nano11082037
|View full text |Cite
|
Sign up to set email alerts
|

Combined Spectroscopic and Computational Study of Nitrobenzene Activation on Non-Noble Metals-Based Mono- and Bimetallic Catalysts

Abstract: In this paper, substituted anilines are industrially obtained by direct hydrogenation of nitroaromatic compounds with molecular H2 using metals as catalysts. Previous theoretical studies proposed that the mechanism of the reaction depends on the nature of the metal used as a catalyst, and that rationally designed bimetallic materials might show improved catalytic performance. Herein, we present IR spectroscopic studies of nitrobenzene interactions with monometallic Ni/SiO2, Cu/SiO2 and Pd/SiO2, and with bimeta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The selectivity of Ni catalysts has been constrained because most supported Ni catalysts are active for the reduction of the nitro group as well as for other unsaturated functional groups (e.g., C=C and C=O) existing in the same substrate. Various supports have been used for Ni-based catalysts [36][37][38][39], including γ-alumina, silica, carbon fibers, graphene/carbon nanotubes, and molybdenum disulfide, to overcome these difficulties. All these works indicate that the choice of support material is essential.…”
Section: Introductionmentioning
confidence: 99%
“…The selectivity of Ni catalysts has been constrained because most supported Ni catalysts are active for the reduction of the nitro group as well as for other unsaturated functional groups (e.g., C=C and C=O) existing in the same substrate. Various supports have been used for Ni-based catalysts [36][37][38][39], including γ-alumina, silica, carbon fibers, graphene/carbon nanotubes, and molybdenum disulfide, to overcome these difficulties. All these works indicate that the choice of support material is essential.…”
Section: Introductionmentioning
confidence: 99%
“…bisbenzene chromium 45 ). The optimised structure for nitrobenzene adsorbed on Pd(111) was recently reported by Milla ´n and co-workers 24 as occurring in a parallel orientation via binding of the phenyl group and via a single N-OÁ Á ÁPd, with the C-H bonds distorted from the plane of the molecule and the NO 2 group twisted with respect to the phenyl ring. In contrast, our calculations show perpendicular adsorption results in only minimal changes in the molecular geometry.…”
Section: Computational Studiesmentioning
confidence: 90%
“…This perspective meshes with a recent spectroscopic and computational study by Milla ´n and co-workers on nitrobenzene activation on non-noble metals-based mono-and bimetallic catalysts. 24 This article concentrates on the adsorption of nitrobenzene over a 5 wt% Pd/Al 2 O 3 catalyst (GU-1) that is a model for low metal loading Pd/Al 2 O 3 aniline synthesis catalysts intended for operation at elevated temperatures. 8 The performance of this catalyst in vapour phase nitrobenzene hydrogenation has previously been described, 8 as has the morphology of the Pd crystallites.…”
Section: Introductionmentioning
confidence: 99%
“…12 DFT calculations showed that flat-lying reactive C 6 aromatic molecules interact with four metal atoms on pure transition-metal surfaces and require extended clusters and subsurface transition-metal atoms in Cu-based alloys. 38,39 However, because of the isolated nature of transition metals, this flat-lying adsorption mode is not possible on SAAs, on which styrene likely prefers to interact with the dopant via the vinyl substituent. Many authors have indeed reported a di-σ adsorption geometry for ethylene on SAAs.…”
Section: ■ Adsorption On Single-atom Alloysmentioning
confidence: 99%
“…In fact, Kyriakou et al experimentally showed that styrene could be selectively hydrogenated to ethylbenzene on PdCu(111) SAA . DFT calculations showed that flat-lying reactive C 6 aromatic molecules interact with four metal atoms on pure transition-metal surfaces and require extended clusters and subsurface transition-metal atoms in Cu-based alloys. , However, because of the isolated nature of transition metals, this flat-lying adsorption mode is not possible on SAAs, on which styrene likely prefers to interact with the dopant via the vinyl substituent. Many authors have indeed reported a di-σ adsorption geometry for ethylene on SAAs. ,,,, Gao et al were able to rationalize the relative affinity of different SAAs for ethylene based on molecular orbitals (d xz and d z 2 of the dopant and π and π* of ethylene) .…”
Section: Adsorption On Single-atom Alloysmentioning
confidence: 99%